2020
DOI: 10.5624/isd.2020.50.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and perceptions regarding the future of artificial intelligence in oral radiology in India: A survey

Abstract: Purpose: This study investigated knowledge, attitudes, and perceptions regarding the future of artificial intelligence (AI) for radiological diagnosis among dental specialists in central India. Materials and Methods: An online survey was conducted consisting of 15 closed-ended questions using Google Forms and circulated among dental professionals in central India. The survey consisted of questions regarding participants' recognition of and attitudes toward AI, their opinions on directions of AI development, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 14 publications
3
43
1
3
Order By: Relevance
“…The awareness rate among dentists is considerably high in our study than medical students and surgeons in Pakistan as evident from previous researchers (15,16). A similar finding was published from India that reported 68% of dental practitioner had familiarity with the concepts of AI (17).…”
Section: Discussionsupporting
confidence: 82%
“…The awareness rate among dentists is considerably high in our study than medical students and surgeons in Pakistan as evident from previous researchers (15,16). A similar finding was published from India that reported 68% of dental practitioner had familiarity with the concepts of AI (17).…”
Section: Discussionsupporting
confidence: 82%
“…The authors stated that 51% of the participants believe that the key role of AI would be the analysis of complicated radiographic scans, and 63% agree that artificial intelligence has a future in India. The study found that dentists are well aware of artificial intelligence, that artificial intelligence programs can be used by dentists as an auxiliary method to improve diagnostic sensitivity when interpreting radiographs, and that artificial intelligence has a promising role in radiological diagnosis (3).…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence (AI) can be defined in simple terms as using computers or machines to perform tasks that normally require humans (1)(2)(3)(4)(5). Machine learning, which is a branch of artificial intelligence, can be used to teach machines and computers how to interpret different kinds of data using various algorithms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations